Comments on the KKM theory on hyperconvex metric spaces - Park, Sehie (Tamkang Journal of Mathematics, 2010)
Recent results in the KKM theory on abstract convex spaces and the related multimap classes $\frak{KC}$ and $\frak{KO}$ are applied to deduce generalizations of results on KKM maps in metric spaces in Amini et al. [1] and generalized KKM theorems on hyperconvex metric spaces in Chang et al. [4, 5].